Pilot study GPIB control of HP54600 digital oscilloscope / Zuhaina Zakaria and Bibi Norasiqin Sheikh Rahimullah - Zakaria, Zuhaina; Sheikh Rahimullah, Bibi Norashiqin (1996)
Today's research and manufacturing engineers arc being pressured to improve productivity while reducing costs. Testing and measurement must be accomplished in the shortest possible time and in the most repeatable manner. In this project, we adopt a general purpose interface bus (GPIB) controller using the serial COM port of the PC and design test software to control communication between the PC and the HP54600A oscilloscope. We also design object libraries for test and measurement for the HP54600A oscilloscope and finally write sample program to automate measurement using the PC.